the PERHITUNGAN PROYEKSI PENDUDUK DAN KONDISI KETENAGAKERJAAN DI KOTA PEKANBARU: PERHITUNGAN PROYEKSI PENDUDUK DAN KONDISI KETENAGAKERJAAN DI KOTA PEKANBARU - rizki amelia, hutri (Journal of Geography Science and Education, 2024)
The aim of this research is to obtain information about future growth projections related to employment conditions in Pekanbaru City. The type of research used is quantitative descriptive research with a secondary data analysis approach. Data was obtained from BPS Pekanbaru City, in this case the secondary data used is population data for Pekanbaru City for 2023. This research was carried out by calculating the population data for Pekanbaru City and presenting the results of these calculations as a finding, using the exponential projection method. The research results show that the population of Pekanbaru City experiences a significant increase every year. This is caused by several factors, including the high rate of migration of Pekanbaru City residents, both coming from outside Pekanbaru City and from outside Riau Province. If viewed from its geographical location, Pekanbaru City is in a strategic position so that many residents from surrounding provinces migrate to Pekanbaru City. Of course, this is also supported by advances in information technology, communication and transportation as well as smooth accessibility. Population growth will definitely be followed by growth in the number of working age people. This growth in the working age population will have an impact on employment conditions. Based on analysis of Pekanbaru City population data, it is known that the highest unemployment rate is from high school education, namely 14,721 people, and second place is followed by undergraduate graduates, namely 9,577 people. From these data it is known that the unemployment rate is dominated by educated unemployment